DEVELOPMENT OF IT-BASED PAI LEARNING MEDIA - Huda. M, Samsul; Hidayat, Noer Fadli; Najiburrahman, Najiburrahman (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This article aims to enable learning to progress and develop to become more effective and efficient. Apart from that, Islamic religious education also aims to develop attitudes and characters loyal and devoted to Allah SWT and in line with current realities. All educational institutions must be proactive, creative, and productive when reading current phenomena. Therefore, the role of IT is vital here, creating good designs as a basis for advances in information and communication technology, adding Islamic religious education learning activities with materials and skills and practising religion, including learning and mastery activities. However, we must also be able to use a technical approach with learning methods using the internet program